RESEARCH OF ULTRASONIC PROCESSING OF WATER ON THE GERMINATION OF SUGAR BEET SEEDS - Ківа, О. В.; Грибініченко, В. В. (Scientific Progress & Innovations, 2013)
Experimental studies have been conducted to determine the effect of ultrasonic pre-treatment of water on germination and vigor of seeds of sugar beet. Experimental studies have been conducted to determine the effect of duration of ultrasonic treatment on vigor. Served results of experimental tests and obtained characteristics of the process of seed germination of plain water from the municipal water supply and water that previously was subjected to ultrasonic treatment and a comparative analysis are conducted.